Phosphors, Up Conversion Nano Particles, Quantum Dots and Their Applications Volume 1 - Liu, Ru-Shi.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book introduces readers to fundamental information on phosphor and quantum dots. It comprehensively reviews the latest research advances in and applications of fluoride phosphors, oxide phosphors, nitridosilicate phosphors and various quantum dot materials. Phosphors and phosphor-based quantum dot materials have recently gained considerable scientific interest due to their wide range of applications in lighting, displays, medical and telecommunication technologies. This work will be of great interest to researchers and graduate students in materials sciences and chemistry who wish to learn more about the principles, synthesis and analysis of phosphors and quantum dot materials.
Introduction to the basic properties of luminescent materials -- Phosphors for White-light LEDs through Principle of Energy Transfer -- Energy Transfer Between Luminescent Centers -- Principles of Energetic Structure and Excitation Energy Transfer Based on High Pressure Measurements -- First-principles calculations of structural, elastic, electronic and optical properties of pure and Tm2+-doped alkali-earth chlorides MCl2 (M=Ca, Sr and Ba) -- First-principles calculation of luminescent materials -- Color Tuning of Oxide Phosphors -- Oxide Phosphors -- Categories of Oxide Phosphors -- Crystal structures and Luminescence properties of oxyhalide-based phosphors -- Tuning of luminescence by varying the O/N or Al/Si ratio in some Eu-doped nitride phosphors -- Characteristics and properties of A(I,II)M(IV)F6 fluoride phosphors -- Novel Phosphors for UVLEDs -- Bismuth doped photonic materials: are they promising phosphors for WLEDs? -- Design of single-phased multicolor-emission phosphor for LED -- Crystal Structure and Luminescence Properties of Some Fluorides, (Oxy)nitrides and Oxides Phosphors.
Keywords: Inorganic chemistry; Materials; Nanotechnology; Inorganic Chemistry; Materials Engineering; Nanotechnology